The effects of the institutional environment on entry mode choice of foreign firms. - Choi, Hannah Jia Yi. (2011)
In light of our increasingly globalized environment, international expansion has become an essential strategic move for firms who want to survive in this competitive global landscape. The choice of foreign entry mode when expanding is thus a critical decision for senior management. Current research on foreign entry mode choice mostly focuses on the transaction cost economics approach and resource-based view. These two views emphasize firm and industry factors, while considering the effects of country-specific contextual factors as constant or less important variables. The neglect of these contextual factors has raised concern over the assumption that one can simply overlook the different country environments in which entry mode strategies are adopted. Hence, the key purpose of this study is to investigate the effect of the institutional environment on entry mode choice. Analysing a sample of 1,252 firms from 39 countries entering into China, we examine the effect that the institutional environment has on the entry mode choice. Our results support the hypothesis that the institutional environment does affect the choice of entry mode. Specifically, our findings show that normative institutional factors like home-country uncertainty avoidance and in-group collectivism do have predictive power over the entry mode choice. These findings have strong implications for policy makers as it shows that institutional factors cannot be ignored when considering the impact of policy changes on the entry mode choice decision.